Combined effects of food additives and heat treatment on fruit rot disease and quality of harvested dragon fruit - Jitareerat, Pongphen; Sripong, Kanlaya; Masaya, Kato; Aiamla-or, Sukanya; Uthairatanakij, Apiradee (Agriculture and Natural Resources, 2018)
The effects of food additives (sodium carbonate, SC and potassium sorbate, PS) at 0%, 1%, 2%, 3% and 4% weight per volume on fungal spore germination of dragon fruit rot diseases, Colletotrichum gloeosporioides, C. capsici and Fusarium sp. were investigated on media. PS at all concentrations showed complete inhibition of spore germination in the three fungi. SC 2% inhibited the germination of C. gloeosporioides by 100% while SC 3% completely inhibited the germination of C. capsici and Fusarium sp. PS solution was selected to study its combined effects with hot water treatment on fruit rot disease and quality of dragon fruit artificially inoculated with C. gloeosporioides. The fruit samples were treated in a heated (55 °C) solution of 1% PS for 5 min and then cooled in tap water at 10 °C (PS-55 °C + cold H2O). Non-treated fruit and fruit treated with the fungicide carbendazim were used as controls. All samples were assessed after being kept at 13 °C for 15 d. The treatment of PS-55 °C + cold H2O reduced the severity of diseases and helped to delay chlorophyll degradation in the dragon fruit bracts, had little impact on the respiration rate, delayed ethylene production and maintained the total ascorbic acid content. However, PS- 55 °C + cold H2O treatment, while having little initial effect, did reduce fruit firmness after 15 d of storage. The PS-55 °C + cold H2O treatment did not affect weight loss or the total soluble solids concentration. These findings showed that the PS-55 °C + cold H2O treatment could act as a safe alternative method for suppressing fruit rot disease while maintaining the quality of dragon fruit during cold storage.